A Multimodal Discourse Analysis of Wardah Cosmetics Advertisement - Nur Alifah; Agus Rohmat Hidayat (Jurnal Impresi Indonesia, 2024)
This research paper presents a comprehensive multimodal discourse communication (MDC) of a selected advertisement from Wardah Cosmetics. This research explores the analysis of multiple modes of advertising for Wardah Islamic beauty products. The research employed a descriptive qualitative approach to examine visual elements present in Wardah beauty advertisements. It incorporated the Bahasa Halliday Metafunction component and the multimodal discourse analysis framework Kress and Van Leeuwen developed. Through this analysis, the research aims to provide valuable insights into the discursive strategies employed by the brand and shed light on how the advertisement constructs and shapes cultural meanings, identities, and beauty ideals. The findings of this research contribute to the field of multimodal discourse analysis and offer practical implications for advertisers, marketers, and scholars interested in understanding the complex dynamics of persuasive communication in the context of cosmetics advertising.